Effectiveness of STS-C-based multimodal science materials on primary students' digital science literacy and global character - Novi Yuliyanti; Sarwi; Sri Wardani; Siti Fathonah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study analyzes the effectiveness of Science, Technology, Society, and Culture (STS-C) based multimodal science materials in enhancing digital science literacy and global character among fifth-grade students. This quasi-experimental study employed a Non-equivalent Control Group design involving 64 students. Data gathered via digital science literacy tests, global character questionnaires, and observation sheets were analyzed using ANCOVA and N-Gain scores. The experimental group showed a significant increase in digital science literacy (mean post-test: 88.65; N-Gain: 0.74, high) and global character (mean post-test: 84.30; N-Gain: 0.58, medium). The analysis showed a significant difference in outcomes compared to the control class (p < 0.001). Conclusion: STS-C-based multimodal materials are effective in enhancing students' scientific understanding and internalizing global citizenship values within local cultural contexts. This study contributes a theoretically modeled instructional framework that bridges digital technology with socio-cultural elements in primary science education.